Study of puncher materials for singulation process in semiconductor manufacturing industry / Vikram Nanthanar - Vikram, Nanthanar (2019)
Punching or Singulation is one of the most common processes used in many semiconductor industries as a separation process from a substrate which contain four to nine units. Having a basics understanding of the material to be used in the punching process can help to improve the tool life thus can increase the quality of the end product in various ways. In the high volume of production, improving the tool life such as puncher can save not only tooling material but also could reduce the change of the tool over the time. Even though the carbide material is in use for the past few years, it seems to fail during mass production. In order to improve the puncher material, the 440 C Martensitic Stainless Steel is introduced in this research to replace the existing carbide material. 440 C Martensitic Stainless Steel is a high carbon straight chromium high hardenability martensitic stainless steel, generally provided in the galvanized condition is fabricated with an appropriate angle of the puncher. The function of the puncher's angle is to have a gradual shearing force. When sufficient shearing force is applied, the shear stress in the material will exceed the ultimate shear strength and the material will fail and separate at the cut location. It was observed that the puncher using with 440 C Martensitic Stainless Steel able to sustain premature breakage thus improve the Overall Equipment Effectiveness (OEE).